Sustainability analysis of tuna (Thunnus sp.) management in 11 Fisheries Management Areas 573 Malang District, East Java, Indonesia - DAVID HERMAWAN (Society for Indonesian Biodiversity, 2025)
Abstract. Hermawan D. 2025. Sustainability analysis of tuna (Thunnus sp.) management in 11 Fisheries Management Areas 573 Malang District, East Java, Indonesia. Biodiversitas 26: 2662-2673. The sustainability of tuna management in Indonesia, especially in Fisheries Management Areas (FMA) 573, Malang District, East Java, Indonesia, is essential to guarantee that tuna resources are used sustainably over the long term without harming the marine ecosystem. One of the key challenges in tuna management is striking a balance between the economic exploitation and conservation of fishery resources. This study seeks to assess the sustainability of tuna resource utilization and the factors that will affect the long-term sustainability of its management. The research examines three primary dimensions of sustainable development: the ecological, economic, and social dimensions. The study was conducted from October to December 2024 at Sendang Biru, Malang, East Java, Indonesia. A quantitative research approach was used, incorporating primary data and the MDS-Rapfish data analysis method. The findings of the study indicate that the current management of tuna (Thunnus sp.) in FMA 573, Malang, is classified as fairly good, with sustainability indices ranging from 56.30 to 59.50, categorized as quite sustainable. The highest level of sustainability is calculated in the economic aspect, with a score of 59.50 (quite sustainable), followed by the ecological aspect at 58.13 (quite sustainable) and the social aspect at 56.30 (quite sustainable). Three key factors that significantly affect the sustainability of tuna management in FMA 573, Malang, include: (i) the decline in the size of fish caught, (ii) cost of trip, (iii) compliance with laws and regulations.